2023
DOI: 10.1149/1945-7111/ad0076
|View full text |Cite|
|
Sign up to set email alerts
|

Electrolytic Etching of Germanium Substrates with Hydrogen Peroxide

Joseph G. Wood,
Luke van Buuren,
Ziang Guo
et al.

Abstract: Anodic electrolytic etching of germanium has been performed in hydrogen peroxide etchants with controlled external conditions. In-situ current and ex-situ etch-depths were measured and tracked with respect to etchant composition and stir rates. Gas bubbles formed during the etching process were found to cause non-uniformity in etch-current and surface quality. The effects were minimized in specific composition spaces. Quantitative analysis revealed a linear correlation of the number of electrons transferred du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…After each intermittent CV acquisition the observed current resets to its peak value of approximately −11 mA. We have previously shown that the integrated current is directly correlated to the total mass of etched germanium 2 . Hence, the difference in the shaded areas underneath the curves in Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…After each intermittent CV acquisition the observed current resets to its peak value of approximately −11 mA. We have previously shown that the integrated current is directly correlated to the total mass of etched germanium 2 . Hence, the difference in the shaded areas underneath the curves in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Germanium is a promising alternative for next-generation backside imagers since recent homoepitaxial growth has yielded extraordinarily low defect densities. [1][2][3][4] The intrinsic properties of germanium enable high-speed hard X-ray detection, and absorption in the near-infrared regime where silicon is essentially transparent. 1,5 Furthermore, germanium is suited as a potential foundational material in the growing field of quantum computing.…”
mentioning
confidence: 99%